Avaliação da força dos músculos do assoalho pélvico e da função sexual de primigestas e nuligestas - Santos, Marília Duarte dos (2017)
Introduction: Hormonal changes and compensatory mechanisms generated during pregnancy can have negative effects on pelvic floor muscles (PFM), which may predispose to muscle weakness. And the PFM weakness, in turn, may impair the sexual function of these women in this period. Objective: To evaluate the relationship between the pelvic floor muscles strength and the sexual function of primigravid and non-pregnant women. Material and methods: Observational cross-sectional study. A sample consisting of 159 women, 81 primigravid and 78 non-pregnant women, who obeyed the following inclusion criteria: being non-pregnant nulliparous women or primigravid, with gestation from the 14th week of gestation, with a single fetus; and report at least one sexual relationship in the last four weeks. Exclusion criteria were: inability to contract the PFM, prior urogynecological surgery and urinary infection. PFM strength was assessed by vaginal palpation, quantified by the Modified Oxford Scale, and by vaginal squeeze pressure through Peritron™. Three voluntary maximum contractions sustained were performed for five seconds and one minute interval between them in each method. Sexual function was assessed using the Female Sexual Function Index (FSFI) questionnaire. Data were statistically analyzed using the SPSS V21 software, using the t, chi- square, Mann-Whiney and Spearman correlation tests. The data are expressed as median (range). Values of p<0.05 were considered significant. Results: Women with sexual dysfunction had lower PFM strength when compared to women without sexual dysfunction, vaginal palpation (2(1-4) and 4(2-5), p<0.001, respectively) and vaginal squeeze pressure (17.5(6.8-39) and 36.8(17-57.1), p<0.001, respectively). The primigravid group presented worse sexual function (FSFI total score: 25.7(14.6-32.4) and 30.6(14.6-36), p=0.004) and lower PFM strength (vaginal palpation: 3(1-4) and 4(1-5), p=0.006, vaginal squeeze pressure: 23(6.8-57.1) and 32.1(9.5-56.7), p<0.001) when compared to the non-pregnant women group. The second-trimester primigravid presented greater PFM strength and higher scores in the orgasm, excitation and pain domains, as well as in the FSFI total score when compared to the third trimester primigravid. A strong positive correlation was observed between the FSFI score and the PFM strength assessment methods. Conclusion: Women with sexual dysfunction had lower PFM strength. The primigravid presented worse sexual function and lower PFM strength when compared to the non-pregnant women. Primigravid in the second gestational trimester showed higher PFM strength and better sexual function than the primigravid in the third trimester. Women with higher FSFI scores had higher PFM strength. Keywords: Pregnant women. Muscle Strength. Pelvic floor muscles. Sexual function.